SARS-CoV-2 Treatment Approaches: Numerous Options, No Certainty for a Versatile Virus - Iacob, Simona; Iacob, Diana Gabriela (Frontiers in Pharmacology, 2020)
SARS-CoV-2 is the most recent coronavirus which crossed the species barrier and led to a rapid and still ongoing pandemic. The SARS-CoV2 infections proved once again that viruses leave a very short window for an action can be taken, too short for adequate antiviral options. In the absence of a specific antiviral treatment, the current armamentarium is based on the analogies with other coronaviruses, other infectious agents or other non-infectious diseases such autoimmune diseases. These therapies can be classifies depending on the targeted pathogenic step into molecules which prevent viral entry, molecules directed against intracellular processes and molecules which modulate the immune response. Numerous drugs have thus entered a fierce competition against an extremely versatile virus. Despite the worldwide acceptance of certain molecules, their efficiency in preliminary studies is still unclear .The article revises the current therapeutic options but advises towards a more cautious and individualized approach.